IMPLEMENTASI METODE WEIGHTED PRODUCT (WP) DALAM MENENTUKAN SISTEM PENDUKUNG KEPUTUSAN PENERIMA BEASISWA KURANG MAMPU - Buhori Muslim; Desi Puspita; Riduan Syahri (P3M Institut Teknologi Pagar Alam, 2023)
In determining the recipients of underprivileged scholarships, so far it is still manual, where there is a buildup of data, errors and is not right on target in determining recipients of scholarships for underprivileged students. The aim of the research is to implement the Weighted Product (WP) method in determining the decision support system for scholarship recipients The stages in the Weighted Product (WP) method are the normal values ​​obtained from the criteria, normalizing the power of each criterion, calculating Vector S, calculating Vector V and ranking of each alternative on all attributes. The results of the calculation of the WP method for the selection of underprivileged scholarships in the 1st alternative are obtained with a ranking value of 0.074361. For testing using Blackbox Testing with alpha testing and beta testing. Where the results of alpha testing tests carried out by experts are database testing with an average value of 3.8 valid information, Interface with an average value of 3.5 valid information, Programming with an average value of 4.0 very valid information, Functional with an average value of 3.8 valid information and the results of beta testing testing, namely with the user an average value of 4.2 with valid information.